The Militia’s Strategy in Using Public Information Space (Media Strategy of Militia to Reform the Organization Image in Bali) - Pascarani, Dewi; Nyoman, Ni (KnE Social Sciences, 2019)
This study examines the media strategy developed by the militia in Bali, a civil troop organizes itself into a security service. Bali has experienced massive tourism industrialization meaning security services are required. Unfortunately, these groups are often associated with “premanism” (thuggery). In the period of 2012 – 2016, these militia groups spent much energy reforming their organizations’ image. Various strategies have been developed, using public information space to expose their organizations’ brand of populism. The research question then, is what media strategy has the militia adopted to reform their organizations’ image? To answer this question, data was collected by interview, observation and documentation. This research found that the types of publicity used by mass organizations in Bali are primarily pure publicity and paid publicity. Pure publicity can be seen at every celebration of religious holidays. The three main mass organizations in Bali seem to compete to congratulate the holidays with large billboard campaigns on the edge of the highway. On most occassions, the billboards also display photos of the leaders of these mass organizations. These leaders claimed that the initial purpose of installing the billboards was both to show a sense of tolerance towards other religions and to highlight the existence of these organizations. Paid publicity is usually undertaken in the form of advertorials. Meanwhile, they also use social media to publicize their social activities. Different from the traditional media they use, their social media represents their populist image as a tolerant social organization under the cultural wisdom “Ajeg Bali”, reflected by the use of Balinese Gods, weapons and colors as their symbols. Keywords: Media strategy, Militia, Public information space.